Gambaran Perilaku Hidup Bersih dan Sehat dengan Kejadian ISPA pada Balita di Wilayah Kerja Puskesmas Malata Kecamatan Tana Righu Kabupaten Sumba Barat Tahun 2024 - Riris I. M. Sogara; Indriati A.T. Hinga; Soleman Landi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Clean and Healthy Living Behavior is a form of manifestation of healthy living orientation which aims to improve, maintain and protect health. A problem that often occurs in Indonesian society is clean and healthy living behavior which has an impact on physical health, one of which is acute respiratory infections. The aim of this research is to determine the description of clean and healthy living behavior with the incidence of ARI in toddlers in the Malata Community Health Center Work Area in 2024. This type of research is descriptive qualitative with a cross-sectional study approach. This research was conducted in February-March 2024 The sample used was 44 respondents, data collection used questionnaires and observations. The results showed that mothers' knowledge was in the sufficient category (63.3%), in the good category (22.7%) and in the poor category (13.6%), the smoking behavior of family members was in the frequent category (72.7%) and the rare category. as many as (27.3%), the physical condition of the house which meets the requirements is (40.9%) and which does not meet the requirements as much as (59.1%), the condition of the external environment of the house which meets the requirements is (25.0%) which does not 33 houses (75.0%) fulfilled the requirements. It is hoped that the community can implement clean and healthy living behavior by paying attention to standards of cleanliness and suitability of the house, as well as ventilation so that air exchange can occur, thereby helping to minimize or prevent acute respiratory infections in toddlers.